William Butler Yeats i Wielkanoc 1916, czyli wypisy z wysokiego modernizmu - Pietrzak, Wit (Poznańskie Studia Polonistyczne. Seria Literacka, 2014)
The article proposes to read the poem by William Butler Yeats Easter 1916 in order to trace its relationships with the poetics of High Modernismrepresented by Ezra Pound, Thomas Staerns Eliot and James Joyce.During the analysis not only the historical and literary background ofthe poem is presented but also the relationship between the poet’s imaginationand the realities around him. Easter 1916 is regarded as one ofthe greatest works of modernist poetry.